Answers>Maths>IB>Article

How do I derive the indefinite integral of sine?

The integral of sine is pretty easy to remember as it is -cos + C. However you need to be able to prove this, without using the integral of cosine. This method uses sines exponential form.

As eiθ​ = cosθ + isinθ, sine can be expressed as sinθ = (eiθ​- e-iθ​) / 2i. This can make the integration easier as the indefinite integral of ekx = (1/k)ekx and the indefinite integral of e-kx = (-1/k)e-kx

Thus ∫sinx dx = ∫(eix- e-ix) / 2i dx = (1/2i)[ ∫eixdx - ∫e-ix dx] = (1/2i)[eix/i + e-ix​/i] + C =  [-(eix​ + e-ix) / 2]  + C.

Now just as sine can be expressed using complex numbers so can cosine such that cosθ = (eiθ​ + e-iθ​) / 2.

Thus  ∫sinx dx = [-(eix​ + e-ix) / 2]  + C = - cosx + C

Answered by Lucile C. Maths tutor

2361 Views

See similar Maths IB tutors

Related Maths IB answers

All answers ▸

Having x(x+4)=y, calculate dy/dx


Determine the coefficient of y^3 in the binomial expansion (2x-3y)^4


Solve the equation log(1-x) - log(x) = 1 where log() is the logarithmic function, base 10.


What is the area enclosed by the functions x^2 and sqrt(x)?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences